THE EDUCTION THOUGHTS OF SAYYID QUTB IN THE TAFSIR OF FI ZILAL AL-QUR’AN - Sobrun Jamil; Ali Yakub Matondang (State Islamic University of North Sumatra Indonesia, 2017)
This research aimed to know the Islamic conceptual framework by Quṭb included of the goal of Islamic Education, mattes of Islamic Education and the methods of Islamic Education, and the relevances between Quṭb concept and recently education. To get the result, writer used two resources of research both are the primary resources and secondary resources. Fī Ẓilāl Al-Qur’ān was the primary resources in wich the verses of the goal of Islamic Education, mattes of Islamic Educatin and the methods of Islamic Education analized by mauḍū’ī method. Secondary resoruces in this research was the books thas correlated with Quṭb ideas in islamic education and the others were the books of excgesis in Koran.Beside of analyis the results of research were that terms of Islamic education used by Quṭb are at- tarbiyah, at-ta’līm, at-taujīh, adab/at-ta’dib, and tahzīb. CopeptuallyQuṭb used At-tarbiyah al-Ḥarakiyyah, at-tarbiyah al-Qur’āniyyah, at-tarbiyah an-nabawiyyah, at-tarbiyah al-Islāmiyyah, at-tarbiyah al-khuluqiyyah, and At-tarbiyah al-Ijtimā’iyyah. The goal of Islamic education as khalifah, abdullah and ululalbab is corellated to be insānjadīd (new humandkind). The matters of Islamic education of Quṭb derived from tauhid (faith), Koran, ibadah (worship), akhlak (moral), salat (praying) and social eduction that tauhid was the basic of Islamic edutaion matters, so on the Islamic eductation method Quth quoted that methodes must be took from tauhid and Quranic verses to get the muttaqin (pius mankind) as contradiction of fool humankind. Quṭb ideas had relevance with the recent education work in tauhid aspect and moral concept as basic of Islamic education.